Optimizing safety stock in cement industry when the demand during lead-time distributed generalized Gamma fourparameters - Ghafour, Karzan Mahdi; Ramli, Razamin; Zabidi, Nerda Zura (CESER Publications, 2016)
In this paper, probability distribution of demand during lead-time which is generalized Gamma four-parameters is considered in finding the optimal safety stock placement in cement manufacturing. The probability distribution of demand during lead-time is determined when the demand and the lead-time are probabilistic; each one is subject to different probability distribution function.The safety stock depends on the safety factor under certain service level and the standard deviation of demand during lead-time which can be obtained from the distribution.Finally, the quantities of the safety stock represent an optimal value at each position to avoid over or under stock which is the most controversial questions in the inventory system area.